TIPOLOGI EKSPANSI MUSEUM - Arja Wendra Nityasa; Sutarki Sutisna (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
A building of architectural works was created to have a main function so that it could be called a school, office and especially a museum. However, due to the development of the times, the influence of technological advances and changes in people's lifestyles can reduce enthusiasm for the building so that the need for additional space in accordance with the needs of the community, is included in the main functions. However, to make something new it is necessary to pay attention to the context of what was already there. According to Prof. Bill Raun Oklahoma State University academics stated that contextual emphasizes that a building must have a relationship with the environment (buildings that are around it). These linkages can be formed through the process of reviving the specific breaths that exist in the environment (old buildings) into new buildings afterwards The Museum’s Extension Typology Journal wants to show a small part of the design process and rules that need to be considered when designing an expansion of the museum that accommodates new functions that are in accordance with the demands of the community and the times or accommodates the increasing number of showing objects. The analysis process was carried out through observation through sampling ten museum extensions from around the world that were analyzed with the same variables to look for certain patterns and look for relationships between new museum buildings and the old ones. AbstrakSebuah bangunan karya arsitektur diciptakan untuk memiliki sebuah fungsi utama sehingga dapat disebut sebagai sekolah, kantor dan khususnya museum. Namun, akibat perkembangan zaman, pengaruh kemajuan teknologi dan perubahan gaya hidup masyarakat dapat mengurangi antusiasme terhadap bangunan tersebut sehingga perlu adanya kebutuhan ruang tambahan yang sesuai dengan kebutuhan masyarkat, dimasukan ke dalam fungsi-fungsi utama tersebut. Namun, untuk membuat sesuatu yang baru perlu memperhatikan konteks terhadap apa yang sudah ada sebelumnya. Menurut Prof.Bill Raun akademisi Oklahoma State University menyatakan bahwa kontekstual menekankan bahwa sebuah bangunan harus mempunyai kaitan dengan lingkungan (bangunan yang berada di sekitarnya). Keterkaitan tersebut dapat dibentuk melalui proses menghidupkan kembali nafas spesifik yang ada dalam lingkungan (bangunan lama) ke dalam bangunan yang baru sesudahnya. Jurnal Tipologi Expansi Museum ingin menunjukan sebagian kecil proses desain dan kaidah yang perlu diperhatikan saat merancang perluasan museum yang mengakomodasi fungsi baru yang sesuai dengan tuntutan masyarakat dan perkembangan zaman atau menampung benda pamer yang semakin bertambah. Proses analisis dilakukan melalui pengamatan melalui pengambilan sampel sepuluh expansi museum dari seluruh dunia yang dianalisis dengan variabel yang sama untuk mencari pola-pola tertentu dan mencari hubungan antara bangunan museum yang baru dengan yang lama.